Debt Relief and Economic Development in Nigeria: A Review - Adebukola Olubunmi Ayoola; Holiness Oluwafayofunmi C Segun-Olufemi (Fakultas Ekonomi dan Bisnis Islam, 2022)
Nigeria had about 60% (US 18 billion) of its external debt written off by its external creditors in 2005, and this was popularly celebrated in the official quarter as a dividend of democracy. In less than two decades, the country has contracted more loans by successive administrations with the current regime’s call for another debt relief in the outbreak of COVID-19. This paper critically reviewed the processes leading to the reserve and its effect on the socioeconomic well-being of the people from 2006 to 2019. The study relied on secondary data sources, which were analyzed using the content analytical method. Findings revealed that creditors gave debt relief but not necessarily with good intentions. The debtor countries also failed to maximize the benefits as it further fueled the fiscal irresponsibility of a political class, in turn, incurred more debt shortly after a relief at the expense of the people with a huge infrastructural deficit, high rate of unemployment, high poverty rate, low purchasing power, and more negativities. The study concluded that criteria for debt relief should be reviewed with stricter measures to ensure a positive impact on both the economy and the people and prevent a re-occurrence of the vicious debt circle.